Interactive effects of agricultural landscape heterogeneity and weather conditions on breeding density and reproductive success of a diurnal raptor - Kujala, Inga (WILEY, 2025)
Agricultural intensification and climate change are serious threats toward animal populations worldwide. Agricultural intensification reduces the heterogeneity of agricultural habitats by diminishing crop variation and destroying microhabitats, such as small woody features, whereas the effects of climate change range from the growing frequency of weather extremes to disrupted prey-predator dynamics. We collected long-term ringing data from a population of Eurasian kestrels (Falco tinnunculus) located amidst agricultural areas in western Finland during 1985-2021, which we combined with density indices of their main prey species (voles), spatial data consisting of land cover classification of kestrel territories, and weather data, to study the effects of different environmental drivers on breeding density and success. We found that the density of inhabited nests rose with vole abundance and springtime snow depth, with the overall trend of population growth being stronger in areas with more heterogeneous landscapes. Clutch size was influenced negatively by the age of male parent and landscape heterogeneity, and positively by vole abundance, with rainfall having a negative influence conditional to other variables. Likewise, the number of produced fledglings was affected by male age, but it was additionally positively associated with landscape heterogeneity and its interaction with rainfall, with greater fledgling output in heterogeneous landscapes during high precipitation. The discrepancy between factors predicting large clutches and high numbers of fledglings suggests that while kestrels do not prefer heterogeneous landscapes when prospecting for territories, heterogeneous habitats provide better circumstances for foraging during the nestling period, which ensures nestling survival, particularly during adverse environmental conditions. Therefore, breeding in areas under intense agricultural use is more suboptimal to kestrels than their territory preferences would indicate. As changing climate may reduce prey availability and heighten the probability of weather extremities, agricultural intensification may lead to weaker reproductive success in densely populated farmland habitats.The article describes a study that combines long-term ringing data of Eurasian kestrels (Falco tinnunculus), spatial data with land cover classification, density indices of main prey species, and weather data to study the effects of different environmental parameters on breeding density and success of an avian predator in agricultural habitats. We found a discrepancy between factors predicting large clutches and high numbers of surviving fledglings, suggesting that while kestrels do not find benefits to landscape heterogeneity when prospecting for territories, heterogeneous habitats provide better circumstances for foraging during the nestling period, which ensures nestling survival, particularly during adverse environmental conditions. Therefore, breeding in areas under intense agricultural use may be suboptimal to kestrels, particularly under the effects of climate change.image